Achievement of universal health coverage in Surakarta city: policy analysis - Rizky Amalia Puspitaningrum; Ari Probandari; Eti Poncorini Pamungkasari; Tonang Dwi Ardyanto; Ema Nur Fitriana (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Background: Jaminan Kesehatan Nasional (JKN) is the health policy of the Indonesian government to achieve Universal Health Coverage (UHC), where each City or District has a varied regional policy in implementing it. Surakarta City is one of the regions that has been able to reach UHC. Policy analysis triangle is used to understand the various factors involved in each policy process. Objective: This study aims to explore deeply the implementation of JKN policy in Surakarta City to be able to achieve UHC based on a policy analysis triangle.Methods: This type of research is a qualitative study with a case study approach. The study was conducted in Surakarta City, Central Java, from September 2018 to March 2019. Data collection was carried out through in-depth interviews and document analysis. Sampling technique with criterion sampling. The research informants were five people who were the leaders of the Surakarta City Government, and 10 people from the Surakarta City community. Data validity was done by triangulation, member check, and peer debriefing. Results: The implementation of JKN policy in the city of Surakarta to reach UHC was influenced by: actors who were highly committed and competent in the success of the JKN program, a dynamic process in adjusting central policy to the regions by implementing various strategies and innovations to increase JKN membership coverage; political factors with policy making that support the achievement of UHC, environmental factors where population density in Surakarta City is the most densely populated in Central Java, there is a high awareness and willingness of the people of Surakarta City to have JKN, and technological support that facilitates JKN coordination and implementation. Conclusion: Achieving UHC in Surakarta City is the result of optimizing the four factors in the triangle analysis policy.